The Effect of Tempering Heat Treatment on Some Mechanical Properties of Medium Carbon Steel (AISI 1045) Formed By Cold Forging Process - Al-Janabi, Raheem Abd Sayel Muhammad (University of Thi-Qar Journal, 2019)
Current paper discuses the effect of tempering as one of heat treatment processes on some mechanical properties of medium carbon steel (AISI 1045) such as hardness, ultimate tensile strength, yield strength and strain rate , formed by forging hammers operation as one of cold forging process .Three values of loads (20, 30 and 40 ) kg were used in forging operation .The results show that the tempering and cold hammering forging increase the ability of medium carbon steel (AISI 1045) to resist the internal stresses produced by hardening process , so the ultimate tensile strength and yield strength of tempered MCS 1045 decrease with an increase in tempering temperature .Otherwise, the strain rate and hardness of tempered MCS 1045 increases with an increasing of tempering temperature.